2012
DOI: 10.1021/nl303305c
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Tin Nanoparticles during In Situ Sodium Insertion and Extraction

Abstract: The microstructural changes and phase transformations of tin nanoparticles during electrochemical sodiation were studied with a nanosized sodium ion battery using in situ transmission electron microscopy. It was found that the first sodiation process occurred in two steps; that is, the crystalline Sn nanoparticles were initially sodiated via a two-phase mechanism with a migrating phase boundary to form a Na-poor, amorphous Na(x)Sn alloy (x ~ 0.5), which was further sodiated to several Na-rich amorphous phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
444
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(464 citation statements)
references
References 36 publications
16
444
0
4
Order By: Relevance
“…As shown in Fig. 3, we also obtained some shoulders at 0.14 V, 0.27 V, 0.5 V, and 0.8 V those correspond the presence of Na 9 Sn 4 , NaSn, and NaSn 3 metastable phases proposed by Wang et al 21 Furthermore, the first charge capacity was obtained as 619 mAh/g that corresponds to formation of Na 11 Sn 4 phase as calculated by Eq. (2).…”
supporting
confidence: 67%
“…As shown in Fig. 3, we also obtained some shoulders at 0.14 V, 0.27 V, 0.5 V, and 0.8 V those correspond the presence of Na 9 Sn 4 , NaSn, and NaSn 3 metastable phases proposed by Wang et al 21 Furthermore, the first charge capacity was obtained as 619 mAh/g that corresponds to formation of Na 11 Sn 4 phase as calculated by Eq. (2).…”
supporting
confidence: 67%
“…The SnS NCs exhibited the best rate capability, which had the strongest transformation tendency toward α‐Sn. Wang et al45 used in situ TEM to study the electrochemical sodiation mechanism of Sn nanoparticles in a nanobattery configuration. It was found that pristine Sn could be sodiated in two steps.…”
Section: Size Control Of Sn Anodesmentioning
confidence: 99%
“…Similar to their Li counterparts,1 though sodium‐based system has similar electrochemical reaction characteristics compared to lithium‐based one, the larger ionic radius for sodium ion cause sluggish kinetics and volume change during Na storage, leading to lower capacity, poor cycling and rate properties of the Na storage materials. Recently, major efforts have been devoted to promote the electrochemical performance of Na storage materials, for example, Na x MO 2 ,2, 3, 4, 5, 6, 7, 8, 9, 10 polyanionic framework compounds,11, 12, 13, 14, 15, 16, 17, 18, 19 hexacyanoferrate,20, 21, 22, 23, 24, 25, 26, 27 for the cathode materials, and hard carbons,28, 29, 30, 31, 32, 33 alloys,34, 35, 36, 37, 38, 39, 40, 41 oxides,42, 43 sulfides37, 44, 45, 46 for the anode materials.…”
Section: Introductionmentioning
confidence: 99%